Cauchy Problems for Evolutionary Pseudodifferential Equations over p-Adic Field - Bo Wu; Yin Li; Weiyi Su (Abstract and Applied Analysis, 2014)
We study a class of evolutionary pseudodifferential equations of the second order in t,  (∂2u(t,x)/∂t2+2a2Tα/2(∂u(t,x)/∂t)+b2Tαu(t,x)+c2u(t,x)=q(t,x)), where t∈(0,z] and Tα is pseudodifferential operator in x∈Qp, which defined by Weiyi Su in 1992. We obtained the exact solutions to the equations which belong to mixed classes of real and p-adic functions.